Shotgun metagenomics reveals distinct skin microbial species in allergen-sensitized individuals - Riskumäki, Matilda; Ruuskanen, Matti O.; Mäenpää, Kuunsäde; Ruokolainen, Lasse; Mäkelä, Mika J.; Jousilahti, Pekka; Vartiainen, Erkki; Ottman, Noora; Laatikainen, Tiina; Haahtela, Tari; Alenius, Harri; Fyhrquist, Nanna; et al. (Microbiology Society, 2026)
The Karelian region, which spans the border between Finland and Russia, presents distinct environmental exposures and lifestyles on either side of the governmental border. In the more urbanized Finnish Karelia, allergic diseases are markedly more prevalent than in the more rural Russian Karelia. Prior studies, based on amplicon sequencing, have demonstrated major differences in skin microbiotas between the two populations. However, compositional differences in microbiota between sensitized and non-sensitized (NS) individuals have not been characterized. Here, in a selected population of 112 allergen-sensitized and NS adolescents, we used shotgun metagenomics to characterize the prokaryotic, eukaryotic and viral species in the skin potentially involved in allergic sensitization via distinct environmental exposures. In the more urban Finnish Karelia, the microbiome species composition was associated with IgE-mediated allergen sensitization status, while in the more rural Russian Karelia, the composition was associated with exposure to furry pets. Finnish participants showing high IgE-mediated sensitization to common allergens (allergen-specific IgE >7.5 kU/L) had less Cutibacterium acnes and Malassezia in their skin and displayed weaker interconnectedness of the microbial co-occurrence network compared with NS participants. Moreover, Malassezia restricta strain-level differences were related to allergen sensitization in both Finnish and Russian participants. In summary, we found distinct skin microbiomes between allergen-sensitized and NS participants and tracked the bacterial and fungal species associated with the degree of allergic sensitization in the more urbanized part of the Karelian region. These findings provide new insights into the factors that shape the human skin microbiome and influence allergic diseases.